2014
DOI: 10.1038/srep07589
|View full text |Cite
|
Sign up to set email alerts
|

Induced apoptosis in melanocytes cancer cell and oxidation in biomolecules through deuterium oxide generated from atmospheric pressure non-thermal plasma jet

Abstract: Recently, atmospheric-pressure non-thermal plasma-jets (APPJ) are being for the cancer treatment. However, APPJ still has drawbacks such as efficiency and rise in temperature after treatment. So, in this work, a synergetic agent D2O vapour is attached to APPJ which not only increase the efficiency of plasma source against cancer treatment, but also controlled the temperature during the treatment. OD generated by the combination of D2O + N2 plasma helped in enhancing the efficiency of APPJ. We observed OD induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…The experimental data obtained by our group and by other groups on the RONS demonstrated that H 2 O 2 is one of the main and stable species that can result in structural changes of biomolecules due to its oxidation process and it can enhance anticancer therapy9101235 Therefore, for better understanding, we verified the molecular dynamic simulation using 10% H 2 O 2 with Hb and Mb. We measured the RMSD values, which indicate that the presence of H 2 O 2 does not affect the stability of Hb and Mb structures in MD simulations.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The experimental data obtained by our group and by other groups on the RONS demonstrated that H 2 O 2 is one of the main and stable species that can result in structural changes of biomolecules due to its oxidation process and it can enhance anticancer therapy9101235 Therefore, for better understanding, we verified the molecular dynamic simulation using 10% H 2 O 2 with Hb and Mb. We measured the RMSD values, which indicate that the presence of H 2 O 2 does not affect the stability of Hb and Mb structures in MD simulations.…”
Section: Discussionmentioning
confidence: 64%
“…CAP is therefore extremely appropriate for the sterilization of immobilized microorganisms on a material surface under dry and wet conditions, as well as for a wide variety of other practical applications5678. Additionally, CAP shows promising anticancer activities through apoptosis and cell cycle arrest, which have been shown to lead to the destruction of tumor cells in both in vitro and in vivo experiments910111213. Both anticancer activity and the inactivation of microbes by CAP are due to the generation of plasma agents such as photons, electric field, charged particles, and radicals, all of which have different effects on all biomolecular systems.…”
mentioning
confidence: 99%
“…All the cells were maintained in RPMI and DMEM supplemented with 10% fetal bovine serum, 1% non-essential amino acids, 1% L-glutamine (300 μg/mL), 1% penicillin (100 IU/ml) and streptomycin (100 mg/ml) (Hyclone, USA)323647. Cultured cells were grown at 37 °C, 95% relative humidity and 5% CO 2 and passaged twice a week.…”
Section: Materials Methodsmentioning
confidence: 99%
“…Cell viability was measured by the MTT assay343648. Briefly, 2 × 10 5 cells/well were seeded in 96-well plates and incubated for 12 h at 37 °C in a 5% CO2 atmosphere to allow cell adhesion.…”
Section: Materials Methodsmentioning
confidence: 99%
See 1 more Smart Citation